Pengaruh Pendampingan Berkelanjutan terhadap Kompetensi Sosial dan Kompetensi Profesional Guru Sekolah Dasar Negeri 12 Selatpanjang Selatan - Asmadi, Asmadi; Witarsa, Ramdhan; Masrul, Masrul (Universitas Negeri Makassar, 2023)
Continuous mentoring is one of the ways that principals maintain and improve teacher competence. This research aims to measure how much influence ongoing mentoring has on the social competence and professional competence of teachers at public primary school 12 Selatpanjang Selatan. The method used in this research is quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting the research problem, developing research hypotheses, creating a research design, conducting pretests, conducting experiments, conducting post-tests, processing and analysing data, and drawing conclusions. The research sample totalled 10 teachers, consisting of 5 teachers in the experimental class and 5 teachers in the control class. The data collection techniques used were teacher social and professional competence tests. The results showed that the implementation of sustainable mentoring had a significant effect on the social and professional competence of experimental class primary school teachers. Continuous mentoring must continue to be carried out regularly so that the other two teacher competencies can be improved better.